Helminthfauna of magellanic penguin (Spheniscus magellanicus Foster, 1781) proceeding from Ilha Comprida, South Coast, State of São Paulo, Brazil - Prado, Maria Izabel Barbosa de Medeiros do; Santos-Lopes, Ana Rita dos; Silva, Reinaldo José da [UNESP] (My University, 2011)
The present study aims to identify the helminth fauna of Spheniscus magellanicus Foster, 1781 from the municipality of Ilha Comprida, southern São Paulo State. A total of 28 individuals were analyzed, resulting in an identification of three helminth species: Contracaecum pelagicum Johnston & Mawson, 1942, Cardiocephaloides physalis Sudarikov, 1959 and Tetrabotrium lutzi Parona, 1901. Contracaecum pelagicum and C. physalis were core species, while T. lutzi was considered a satellite species. All individuals examined were infected with at least one species (overall prevalence = 100%). The host specimens were all juveniles and the infection may be associated with food items eaten during migration to the Brazilian Coast.

Este estudio tuvo como objetivo identificar los helmintos parásitos de Spheniscus magellanicus Foster, 1781 de la municipalidad de Ilha Comprida, a lo largo de la costa sur de Sao Paulo, Brasil. Un total de 28 individuos fueron analizados, dando como resultado la identificación de tres especies de helmintos: Contracaecum pelagicum Johnston & Mawson, 1942, Cardiocephaloides physalis Sudarikov, 1959 y Tetrabothrium lutzi Parona, 1901. Contracaecum pelagicum y C. physalis se caracterizan como especies core, mientras que T. lutzise considera una especie satélite. Todos los individuos examinados estaban infectados con al menos una especie, con una prevalencia del 100%. Los especímenes hospedadores fueron todos juveniles y el patrón de la infección puede estar asociado con la alimentación durante la migración a la costa brasileña.
Fauna de helmintos del pingüino de Magallanes (Spheniscus magellanicus Foster, 1781) de la Ilha Comprida, costa sur, estado de São Paulo, Brasil
Keywords: Cestoda; Helminthes; Nematoda; Marine birds; Parasitic diseases; Trematoda; Aves marinas; Cestoda; Enfermedades parasitarias; Helmintos; Nematoda; Trematoda